The indirect relationship between sleep and cognition in the PREVENT cohort: identifying targets for intervention - Tari, Benjamin; Ben Yehuda, Michael; Laurell, Axel Anders Stefan; Ritchie, Karen; Dauvilliers, Yves; Ritchie, Craig W.; Lawlor, Brian; Naci, Lorina; Muniz Terrera, Graciela; Malhotra, Paresh; Watermeyer, Tam; Dudas, Robert; et al. (Frontiers in Sleep, 2023)
Introduction: As the global population ages, the economic, societal, and personal burdens associated with worsening cognition and dementia onset are growing. It is therefore becoming ever more critical to understand the factors associated with cognitive decline. One such factor is sleep. Adequate sleep has been shown to maintain cognitive function and protect against the onset of chronic disease, whereas sleep deprivation has been linked to cognitive impairment and the onset of depression and dementia. Objectives: Here, we aim to identify and explore mechanistic links between several sleep parameters, depressive symptoms and cognition in a cohort of middle-aged adults. Methods: We investigated data from the PREVENT dementia programme via structural equation modelling to illustrate links between predictor variables, moderator variables, and two cognitive constructs (i.e., Executive Function and Memory). Results: Our model demonstrated that sleep quality, and total hours of sleep were related to participants’ depressive symptoms, and that, participant apathy was related to higher scores on the Epworth Sleepiness and Lausanne NoSAS Scales. Subsequently, depressive symptoms, but not sleep or apathy ratings, were associated with Executive Function. Conclusions: We provide evidence for an indirect relationship between sleep and cognition mediated by depressive symptoms in a middle-aged population. Our results provide a base from which cognition, dementia onset, and potential points of intervention, may be better understood.